Cultural and International Aspects of Innovation and Entrepreneurship in Higher Educational Institutions: Towards a Typology of Learning Universities (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The purpose of this paper is to analyse the international and cultural aspects that academic entrepreneurs must take into consideration and propose a conceptual framework dedicated to the analysis of higher educational institutions (HEI) regarding their international settings and the support or hindrance to academic entrepreneurship. We elaborate on the international and cultural aspects to be considered to successfully undertake an academic entrepreneurship journey, such as cultural, administrative, geographical, and economic distances. We deepen our understanding of the cultural distance by summarizing the most used sociological approaches. Then we discuss the personal and institutional factors that can support or hinder entrepreneurship success, such as cultural sensitivity, cultural awareness, and academic learning organization. Finally, we considered the settings allowing entrepreneurs to develop their cultural sensitivity in the academic context and propose a typology of the HEI regarding their settings and management conditions of entrepreneurship regarding their internationalization and cultural awareness. The results allow university managers and professors or students to identify their organization's maturity in terms of international and cultural awareness towards fostering innovation and entrepreneurship.